Roles, trust and skills: a typology of patronage appointments - Panizza, Francisco; Peters, B. Guy; Larraburu, Conrado R. Ramos (2019)
This article contributes to the study of the politics of patronage appointments by creating a typology of patronage roles based on the nature of trust between patrons and appointees and on the skills patrons seek in appointees. Our classification brings together the dispersed literature on patronage roles and can be applied to the study of modalities of patronage across and within countries. We offer preliminary evidence from our study of the politics of patronage appointments in Latin America suggesting that variations in patronage roles can be related to variations in the institutionalization of party systems and to the nature of the links between political actors and voters. Finally, we explore whether the categories identified in our empirical study can be found in other settings. We conclude that our typology can contribute to the study of the impact of modalities of patronage on the quality of public administration and on political governability. - Reproduced.
Keywords: Personnel, Public - Recruitment